Point spread function profile in human myopic model eye - Othman, Shah Farez; Tamchek, Nizam; Muhammad, Farah Diana; Abdul Latif, Amirah; Ithnin, Mohd. Hafidz (Akademi Sains Malaysia (ASM), 2025)
Heretofore, eye modelling is based on the emmetropic eye taking its ocular optical components value from the population-based studies. Howbeit, the effect of aberration of myopic refractive error by modelling the eye using the parameters from ocular biometrics and ray tracing method has not been systematically studied. An objective of this study was to determine the point spread function (PSF) of myopic refractive error using eye modelling and ray tracing technique. Three eye models had been successfully modelled in Zemax software, scilicet, emmetropic Liou and Brennan, myopic Liou and Brennan, and corrected myopic Liou and Brennan. The optical performance of the eye models was analysed using PSF, whereby the PSF is presented in the form of Strehl ratio. A comparison of the two results reveals the Strehl ratio value for myopic Liou and Brennan eye was the lowest compared to its emmetropic model. Further analysis shows that the Strehl ratio of the corrected myopic Liou and Brennan model was higher compared to the uncorrected myopic model. Natheless, the corrected myopic model produced lower Strehl ratio value compared with the emmetropic model of Liou and Brennan. From this research, the accuracy of the Strehl ratios for myopia correction and emmetropia were calculated. It has shown that the accuracy of the Strehl ratio value for corrected myopia was lower.